2018
DOI: 10.1177/0300060518773258
|View full text |Cite
|
Sign up to set email alerts
|

Immunological recovery in patients with pulmonary tuberculosis after intensive phase treatment

Abstract: ObjectivesThis study aimed to examine the change and significance of immune parameters in patients with sputum smear-positive pulmonary tuberculosis (TB) after 2 months of intensive phase anti-TB treatment.MethodsThe immune parameters of 232 cases of sputum smear-positive pulmonary TB were detected before and after 2 months of intensive phase anti-TB treatment and compared with 50 cases from healthy volunteers (controls). The T lymphocyte cell population in peripheral blood was detected using flow cytometry. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 34 publications
1
8
0
1
Order By: Relevance
“…Differently, we found that the PHA results gradually increased after treatment, especially at 6 months of treatment. This is in accordance with previous studies indicating that host immunity is restored after TB treatment [36][37][38]. The lymphocyte response to PHA stimulation reflects the functional potential of them [39], and the increase of PHA results in T-SPOT assay indicates the restoration of lymphocyte function in TB patients after treatment.…”
Section: Discussionsupporting
confidence: 92%
“…Differently, we found that the PHA results gradually increased after treatment, especially at 6 months of treatment. This is in accordance with previous studies indicating that host immunity is restored after TB treatment [36][37][38]. The lymphocyte response to PHA stimulation reflects the functional potential of them [39], and the increase of PHA results in T-SPOT assay indicates the restoration of lymphocyte function in TB patients after treatment.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, ATT is associated with significant reduction in AI [65]. Lee , and TNF-α were measured with the help of ELISA, and concentration of cytokines was found to be decreased after treatment initiation [68]. As in most of the cases, anemia in TB ranges between mild and moderate forms, and ATT alone helps to resolve anemia.…”
Section: Treatmentmentioning
confidence: 99%
“…Some opportunistic infections cause transient CD4+ lymphocytopenia, and their treatment has been related to immune recovery. This transient phenomenon has been described in infections associated with an immune-response mainly mediated by T lymphocytes and mononuclear phagocytic cells, especially with the CD4+ subset of lymphocytes [ 17 , 18 ]. However, this immune response also requires a cytokine release network activation.…”
Section: Discussionmentioning
confidence: 99%
“…Kony et al [ 17 ] report that up to 14% of patients with tuberculosis, HIV-negative, and no other immunosuppressive conditions have CD4 counts below 300 cells/mm 3 . Luo et al [ 18 ], demonstrated that treatment directed at this population was associated with an increase in CD4+ lymphocyte count, as well as a decrease in levels of IL-1B, sIL-2R, IL-6 and TNF-a. Similarly, cryptococcal infection has been consistently correlated with CD4+ lymphocytopenia; however, to date, treatment of cryptococcosis has not been reported to improve lymphocyte counts.…”
Section: Discussionmentioning
confidence: 99%